2017
DOI: 10.1177/1933719116653676
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Leads to an Increased Trefoil Factor 3 Concentration in the Peritoneal Cavity but Does Not Alter Systemic Levels

Abstract: This study analyzed whether trefoil factor 3 (TFF3) is locally elevated and correlated with common biomarkers and inflammatory processes in endometriosis. Peritoneal fluid (PF) was obtained from 50 women and serum from 124 women with or without endometriosis. Experimental endometriosis was induced in female C57BL/6 mice by syngeneic transplantation of uterine tissue to the abdominal wall. Levels of TFF3 in PF of women with endometriosis were significantly increased ( P < .05) and correlated with local levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…TFF peptides have essential roles in the defense and repair of the tissues through various mechanisms that participate in epithelial restitution, cell migration as well as angiogenesis, antiapoptosis, promoting leukocyte migration, and inflammatory immune processes (Cook et al., 1999; Kjellev, 2009). Pathologic expression of TFF peptides has been shown in a variety of chronic inflammatory diseases (Astor et al., 2011; Henze et al., 2017). Regarding periodontal inflammation, very few studies investigated these peptides in saliva or gingival tissues of patients with peridontal disease (Chaiyarit, Chayasadom, et al., 2012; Hormdee et al., 2019; Meesala et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TFF peptides have essential roles in the defense and repair of the tissues through various mechanisms that participate in epithelial restitution, cell migration as well as angiogenesis, antiapoptosis, promoting leukocyte migration, and inflammatory immune processes (Cook et al., 1999; Kjellev, 2009). Pathologic expression of TFF peptides has been shown in a variety of chronic inflammatory diseases (Astor et al., 2011; Henze et al., 2017). Regarding periodontal inflammation, very few studies investigated these peptides in saliva or gingival tissues of patients with peridontal disease (Chaiyarit, Chayasadom, et al., 2012; Hormdee et al., 2019; Meesala et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, women with endometriosis also report abdominal pain, constipation, bloating and intestinal gas (Ek et al , 2015). Henze et al (Henze et al , 2016) investigated women with endometriosis and found that peritoneal fluid TFF3 levels were higher in these women when compared to those without endometriosis. Of note, regardless of endometriosis status, the researchers observed menstrual cycle phase differences in serum TFF3 levels (Henze et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Henze et al (Henze et al , 2016) investigated women with endometriosis and found that peritoneal fluid TFF3 levels were higher in these women when compared to those without endometriosis. Of note, regardless of endometriosis status, the researchers observed menstrual cycle phase differences in serum TFF3 levels (Henze et al , 2016). The difference in the relationship of stool TFF3 and intestinal permeability between those on and off hormone contraception (Table 3) reinforces the importance of considering reproductive status and hormone therapy when testing biomarkers in this predominantly female patient group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Показано усиление влияние экспрессии трефоиловых факторов на клетки ретинобластомы [24]. Также показано участие TFF в патогенезе заболеваний легких [42,48], гинекологических заболеваний [1,26,36], болезни Альцгеймера [39].…”
Section: связь с заболеваниямиunclassified